COMBINATION EFFECT OF NAPHTALENE ACETIC ACID (NAA) AND BENZYL AMINOPURINE (BAP) ON MICROPROPAGATION OF Jatropha curcas L. - Mutia Zahara; Zairin Thomy; Essy Harnelly (Jurnal Natural, 2013)
The combination between Naphthalene acetic acid (NAA) (1-2 ppm) and Benzyl Amino Purine (BAP) (0, 5 and 1 ppm) for micro propagation of castrol oil plant (Jatropha curcas L.) had been studied to induce the callus formation had been studied to induce the callus formation by using the meristem shoot as the ex-plants. The result showed that the combination of NAA 1,5 ppm and BAP 0,5 ppm gave the best result.